(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2015)
Since 1996, professors and students of the Faculty of Architecture and Urbanism, of Universidad Central de Venezuela, (FAU UCV) put ourselves at the service of the people of the Julián Blanco neighborhood. We started in that neighborhood, doing research. We listened to people who were willing and needed to solve problems in their homes, some were simple and others serious (we speak as architects with years of experience). Over the years and the relationship we established with neighbors in need of a home, we were forced to transform our university work, into action research. Then, the material needs required our intervention, consequently, the action research was transformed into what we call action-research-intervention.